(3JbGWYGJ hXjajI JfehjI eMdjIs - (3jhfS(B, (3QMjeIs ((3GdLRGFQ(B:s (3OGQ EjdjGA ddfTQ hGdJhRjY(B,s, 2024)
(3GdGWGQ GdfXQj h GdeaGgjej ddMcGeI h GdJfejI GdeMdjI , fXQjGJ h GSJQGJjLjGJ h feGPL GdJfejI GdeMdjI , GdMcGeI h GfeGW GdJSjjQ GdeMdj GQJHGWGJ JfehjI eJHGOdI (B.s
(3GdeQGLY U(B.213-233s
Keywords: (3GdGOGQI GdYGeIs; (3GdGOGQI GdeMdjIs